RUANG KOMUNITAS TIONGHOA DI GLODOK - Leonardo Leonardo; Dewi Ratnaningrum (Jurusan Arsitektur dan Perencanaan, 2020)
The development of modern urban society tends to have an individual nature and is more aloof to its personal space, where humans should be created as social beings who need interaction and socialization with people around them. Modern times with their technologies make society more selfish and as if they do not need others. To meet social needs in the current modern era, it takes a social container that can accommodate the activities of the surrounding community. The community can meet with each other, socialize and also interact through these social media platforms. Glodok is known as a Chinatown in Jakarta, the majority of the population are Chinese. The Chinese Community Room in Glodok is present as the third room or